Problems Encountered in Virtual Learning of Grade 12 HUMSS Student in Bestlink College of the Philippines in the New Normal Intervention Program: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The researchers identified the pros and cons of the deferens of the new academic Performance learning system in teaching the research subject. In this study, the researchers will finalise suitable information that will give the study its Solution to the problem and make it valid and reliable. The advantages of school online learning from instructors’ perspectives are easy access to online learning platforms, online lectures can be recorded, archived, and shared for future reference, and the exams correspond to the materials presented during the lectures. In contrast, the disadvantages of online learning from instructors’ perspectives are that online learning requires the instructors to have a basic understanding of using digital forms of learning, and online learning lacks credibility in exams and needs better time management. This study revealed that the advantages of school online learning from students’ perspectives are using online for English learning is more interesting than the traditional method and ease of handing over assignments, while the disadvantages of school online learning from students’ perspectives are the high costs of internet services, online learning is not suitable for every topic and online learning requires the submission of a lot of duties and activities.